Implementation of Law Number 26 of 2007 concerning Spatial Planning for Green Open Space in the Form of Construction of Public Park Facilities in Krembung District, Sidoarjo Regency - Zaenal Maarif (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the imlpemntation of law Number 26 to 2007 concerning Spatial Planning in Krembung District, Sidoarjo Regency. Furthermore, it is analyzed regarding its application in the field by means of interviews to find by means of conformity with existing laws.This thesis research uses law number 26 year 2007. In empirical research, the auther will use the sociological juridical method with research carried out derectly in the field, using the metehod of seeing the appropriateness of the application of the law and supported by interview activites.The result of policy research on the implimentation of law number 26 of 2007 are still focused on road procurement. From the result of interviews with villige officials, the community hopes to have a of a garden in krembung District. The problem experiended in park procurement are the lack of budget, the future trem for constraction and the lacj of socialization on the importance of green open space for the community.